Digital activism: A case study of viral-based policy implementation trends - Muliono (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2026)
This study aims to examine how digital activism influences government institutional behaviour, particularly regarding virality-based policies. This research focuses on analyzing three public issues: the suicide of an elementary school student, mining policies, and LPG gas regulations which only received government responses after gaining massive virality. This study employed a qualitative case study and the research focuses on selected viral policy cases that gained significant traction on digital platforms. Data were collected through digital content analysis including social media posts, online news coverage, and official government statements. The study focuses on cases occurring between 2025 and 2026. The research was conducted over a period of about two months, between January and February 2026. The findings shows that digital activism plays a substantial role in accelerating the implementation of government policies. The virality of the cases in question forced the government to implement policies promptly and effectively. Furthermore, these viral-based policies demonstrate a transformation in institutional behaviour, where digital public pressure is increasingly influencing agenda-setting and decision-making processes. The study concludes that, by the presence of digital activism, government behaviour patterns are no longer solely determined by formal and structurally designed policy mechanisms but are heavily influenced by the visibility and virality of an issue within the digital space.